EMPIRICAL STUDY OF CHARACTEROLOGICAL FEATURES OF DISCUSSION OF A SUBJECT WITH A HYSTERIC TYPE OF PERSONAL ORGANIZATION (Pedagogy of Higher and Secondary Education, 2011)
The article is devoted development of ideas of interconnection verbal communication and type of personality's organisation and adaptation of these ideas to modern Ukrainian psychological scientific tradition and their verification by practice.
Keywords: psychoanalysis; psycholinguistic; unconscious; symptom; type of personali ty's organisation